Glycosyl disulfides: novel glycosylating reagents with flexible aglycon alteration. - Grayson, E; Ward, S; Hall, A; Rendle, P; Gamblin, D; Batsanov, A; Davis, B (2005)
[reaction: see text] Glycosyl disulfides have been shown for the first time to be effective glycosyl donors. Glucosylation and galactosylation of a panel of representative alcohol acceptors allowed the formation of 28 simple glycosides, disaccharides, and glycoamino acids in yields of up to 90%. As well as providing a novel class of effective glycosyl donors, the ability to easily alter the nature of the aglycon and the ability to differently activate donors that differ only in their aglycon simply through altering conditions lends glycosyl disulfide donors to their use in latent-active reactivity tuning strategies.